Overcoming Barriers to Inclusion: The Role of Financial Literacy and Digital Divide in Expanding Financial Access in Indonesia - Putra, Fariz Hutama; Suhardjanto, Djoko; Trinugroho, Irwan; Arifin, Taufiq (Journal of Ecohumanism, 2024)
This study explores the impact of financial literacy and the digital divide on financial inclusion in Indonesia using panel data from 35 provinces from 2015 to 2022. This study applies multiple linear regression and robust regression to ensure the consistency and validity of the estimation results. The analysis shows that improved financial literacy significantly contributes to expanding access to and use of formal financial services, especially in areas with limited infrastructure. On the other hand, the digital divide has been found to intensify access inequality, hindering the optimal use of digital financial services, especially in vulnerable communities and rural areas. These findings emphasize the importance of collaboration between the government, financial institutions, and technology providers when formulating integrated policies. Such policies should include inclusive financial literacy programs and digital infrastructure investments to encourage the adoption of digital services while reducing reliance on informal sources of financing. Thus, this research provides new insights for policymakers seeking to strengthen the inclusive financial system and ensure equitable access to financial services for all levels of society.